2019
DOI: 10.1002/alr.22494
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel simulation‐based task trainer for management of retrobulbar hematoma

Abstract: Background Retrobulbar hematoma (RH) is a rare but devastating complication of sinus surgery. It is treated initially with a lateral canthotomy and cantholysis at the bedside. Due to the high stakes and urgency of this complication, teaching this in the clinical setting is difficult. The objective of this study was to develop a cadaveric model for addressing this problem. Methods A fresh‐frozen human cadaveric model of RH was created using a Foley catheter to simulate elevated intraocular pressure. Residents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
2
9
0
1
Order By: Relevance
“…This aligns with the prior reported literature of signi cant improvements in trainee self-con dence following their participation in an ENT boot camp. 1,2,8,9,13,[17][18][19][20] Our data demonstrated that ENT ST3s reported the greatest improvements in self-preparedness in the rigid bronchoscopy station and the greatest improvement in self-con dence in the sphenopalatine artery (SPA) ligation station compared to the other stations (Table 3). While SPA ligation has not been reported in an ENT bootcamp setting, the tracheostomy ndings support the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with the prior reported literature of signi cant improvements in trainee self-con dence following their participation in an ENT boot camp. 1,2,8,9,13,[17][18][19][20] Our data demonstrated that ENT ST3s reported the greatest improvements in self-preparedness in the rigid bronchoscopy station and the greatest improvement in self-con dence in the sphenopalatine artery (SPA) ligation station compared to the other stations (Table 3). While SPA ligation has not been reported in an ENT bootcamp setting, the tracheostomy ndings support the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that ST3 knowledge improved over a two day bootcamp, which along with the literature, provides evidence that knowledge acquisition through bootcamps may help ST3s to transition into their new clinical role more easily. 1,2,8,9,13,[17][18][19][20] Additionally, the inclusion of simulation stations allows ST3s to acquire the technical and non-technical skills expected of ENT ST3's. The literature suggests that bootcamps are a useful adjunct to the traditional apprenticeship training model, as they provide a standardised and equal approach towards the training of ST3's that can integrate the use of performance metrics unlike the variability of clinical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Bei Einblutungen nach Trauma oder nach endonasaler Nasennebenhöhlen Operation mit erheblicher Erhöhung des intraorbitalen Druckes kann als Erstmaßnahme mittels einer lateralen Kanthotomie bzw. einer Kantholyse mit transpalpebraler Eröffnung des Septum orbitale eine Reduktion des intraorbitalen Druckes erreicht werden [26,27]. Die Drucksenkung bei einer lateralen Kanthotomie beträgt bis zu 14,2 mmHg, bei einer Kantholyse 30,4 mmHg [28].…”
Section: Therapieunclassified
“…3 Reports on orbital haematomas secondary to haemostasis disorders have rarely been described in humans. 4,5 Similarly, in dogs, there is a low number of reported cases of retrobulbar haematomas, some being secondary to anticoagulant rodenticide toxicity 6 and one recent report being associated with von Willebrand disease. 7 A case of retrobulbar haematoma secondary to haemophilia A in a dog is described.…”
Section: Introductionmentioning
confidence: 99%